Analisis Penyaluran dan Pengawasan Kredit pada Kopdit (CU) Pardomuan Pakkat Cabang Onan Ganjang - Marbun, Febtri Basaria; Siboro, Danri Toni; Saribu, Ardin Dolok (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to determine whether the distribution and supervision of credit carried out by Kopdit (CU) Pardomuan Pakkat Onan Ganjang Branch is in accordance with the provisions that apply to previous savings and loan cooperatives. The types and sources of data used in this research are primer and secondary data. The data collection methods used in this research are documentation method and interview method. The data analysis method used is descriptive analysis method. Based on the results of research conducted by researchers, the following conclusions were obtained. The credit distribution process carried out by Kopdit CU Pardomuan Pakkat Onan Ganjang Branch is in accordance with the credit distribution process in general. Credit supervision at Kopdit CU Pardomuan Pakkat Onan Ganjang Branch has been effective nd has been carried out according to the rules set and implemented. Suggestions that can be given by the author of this research are. Provide direction and guidance to officers to be committed and consistent. Debtors should be consistent with the rules and credit agreements that have been agreed upon. It is expected to increase supervision of business profits. Credit distribution also needs to be done better so that customers do not misuse credit.